2013
DOI: 10.1002/etc.2112
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the tricyclic antidepressant drugs amitriptyline and nortriptyline in agriculture soils

Abstract: Abstract-Amitriptyline and nortriptyline are widely used tricyclic antidepressant drugs. They have been detected in wastewater, surface runoff, and effluents from sewage treatment plants. As such, they could potentially reach agriculture land through the application of municipal biosolids or reclaimed water. In the absence of data on their fate in the environment, the persistence and dissipation pathways of radiolabeled amitriptyline were determined in three agriculture soils varying widely in texture and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Although, to the best of our knowledge, no literature data are available on the degradation of amitriptyline in sediment, the persistence of the compound has been explored in soil. Our half‐lives are similar to those reported in soils with different textures where DT50s ranging from 34.1 to 85.3 d were observed (Li et al ). In the present study, the dissipation of amitriptyline was suggested to result from the formation of nonextractable residues and the degradation of the parent compound to nortriptyline ( N ‐desmethyl amitriptyline) and amitriptyline‐ N ‐oxide.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although, to the best of our knowledge, no literature data are available on the degradation of amitriptyline in sediment, the persistence of the compound has been explored in soil. Our half‐lives are similar to those reported in soils with different textures where DT50s ranging from 34.1 to 85.3 d were observed (Li et al ). In the present study, the dissipation of amitriptyline was suggested to result from the formation of nonextractable residues and the degradation of the parent compound to nortriptyline ( N ‐desmethyl amitriptyline) and amitriptyline‐ N ‐oxide.…”
Section: Resultssupporting
confidence: 91%
“…For example, soil texture was found to affect the degradation rates of caffeine, with faster degradation being observed in loam and sandy loam soils compared with a silt loam soil (Topp et al ). Amitriptyline also showed faster dissipation in a loam soil compared with clay and sandy soils (Li et al ). Benotti and Brownawell () reported variations in degradation rates for 19 pharmaceuticals in estuarine and coastal surface water samples and suggested that faster rates of pharmaceutical degradation occurred in waters with a greater abundance of total bacteria or the presence of microbial communities that are better able to transform these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These differences highlight the variability in behaviour of this API with the experimental conditions employed. While only a few studies on the persistence of AMI have been documented, these report high persistence in both water (Baena-Nogueras et al, 2017) and agricultural soils (Li et al, 2013), in agreement with the data from this study ( Figure 3G).…”
Section: (2017)supporting
confidence: 92%
“…Antidepressants are frequently prescribed pharmaceuticals used for humans and animals. Amitriptyline is one of the mostly widely used tricyclic antidepressants for treatment of depression, anxiety, and a variety of chronic pain syndromes (Li et al, 2013; Ivetić et al, 2016). It is mainly metabolized by demethylation, forming nortriptyline (Farnoudian‐Habibi et al, 2016).…”
mentioning
confidence: 99%